Ecologia e etnozoologia da família Teredinidae (Mollusca, Bivalvia) em área de manguezal do município de Conceição da Barra, Espírito Santo, Brasil - Silva, Cristiane Alves da (2014)
The Family Teredinidae consists of species highly specialized to boring the wood, being abundant in mangroves due to the high availability of this substrate . This group has great significance because breaks timber and leave exposed their galleries when it dies, facilitating the action of bacteria and fungi, as well as serving as food for invertebrates and vertebrates. Despite their ecological importance, teredinids have been recognized mainly by large losses to the fishing industry, and because of this, most of the studies are related to methods of protection and resistance to various woods to action of these perforating organisms. The knowledge of the group is necessary for their taxonomic, ecological and ethnozoology understandin, especially in the Espírito Santo state, where studies with this taxon are scarce. The general aimed of this work was to determine the Teredinidae fauna in mangrove areas of the municipality of Conceição da Barra. To do this, individuals were obtained through deployment of panels made of laminated plywood and collecting mangrove trunks in decomposition process. The specimens were preserved in 85% alcohol and glycerine in the ratio 5:1 and identified using a stereomicroscope, based on the morphology of the pallets. In trunks collected in São Mateus River were collected, Neoteredo reynei (Bartsch, 1920), Psiloteredo healdi (Bartsch, 1931) and Nausitora fusticula (Jeffreys, 1860); in Itaúnas river were obtained Bankia rochi (Moll, 1931), Neoteredo reynei and Nausitora fusticula. In panels of Itaúnas river were identified the species Neoteredo reynei, Nausitora fusticula, Bankia rochi and Teredo turnerae ( Müller; Lana , 2004), having been collected Neoteredo reynei, Nausitora fusticula, Bankia rochi and Bankia bagidaensis ( Roch, 1931) in the São Mateus river. Of the seven species collected , Bankia bagidaensis is first mentioned to the southeast of Brazil and Psiloteredo healdi, Bankia fimbriatula and Bankia rochi have their first record for the Espírito Santo state. The largest number of individuals found in collectors of São Mateus river is due, probably, the difference in salinity of the two rivers. Besides to working with mangrove trunks and pallets also were made interviews with local fishermen with the aim of knowing the relationship of this community with teredinids, being visible their repulse by individuals. This may be due to the fact that this group doesn't have importance financial/nutritive to those who live in this region. More than taking measures to prevent the boats attack by Teredinidae would need a information job to fishermen about the ecological importance of the group. Based on what was raised in the present study can be said that it is necessary to develop new ecological studies correlating the presence of Teredinidae species with the variation in flood period. Moreover, is indispensable perform sampling efforts in other capixabas mangroves for know the likely new records that may arise and also ethnozoological studies for knowing the relationship of the people that living around mangroves with the group.